Improving Telemedicine through IoT and Cloud Computing: Opportunities and Challenges - M. Sunil Kumar; D. Ganesh (Advances in Engineering and Intelligence Systems)
The rapid evolution of healthcare services has been driven by the convergence of the Internet of Things and cloud computing technologies, inherently transforming telemedicine. This study evaluates the transformative effect of IoT and cloud-based solutions through the telemedicine domain, especially in the remote delivery of healthcare services and medical consultations. It explores how IoT-enabled medical devices facilitate continuous remote patient monitoring and real-time health data collection and emphasizes the role of wearable devices comprising smartwatches and fitness trackers in elevating data accuracy and offering personalized health insights. Cloud computing's key role in telemedicine is investigated through its scalable data storage and processing capabilities, which manage the vast amounts of data generated by IoT devices. The study also discusses the benefits of cloud-based telemedicine platforms, including scalability, accessibility, cost-effectiveness, and the implementation of security measures to address data privacy concerns. The combination of IoT and cloud methods indicates various advantages, such as improving patient outcomes, expanding healthcare accessibility, and enabling data-driven decision-making for medical professionals. Real-world case studies outline successful implementations of these methods, which result in decreased hospital readmissions, improved patient engagement in health management, and centralized critical care expertise. However, significant challenges are addressed, including data security, interoperability, and reliable internet connectivity in various healthcare settings. The reports highlight the necessity of more studies on the integration of artificial intelligence in telemedicine and the adoption of edge computing solutions to overcome cloud-related issues in low-connectivity scenarios. This study provides valuable insights into redefining telemedicine in the digital era and serves as a guide for future developments in healthcare technology.